Hubungan Higienitas Vagina, Kadar Gula Darah dan Kadar Hormon Estrogen dengan Kejadian Kandidiasis Vaginalis - Silfina Indriani; Netti Suharti; Almurdi Almurdi (Universitas Batanghari Jambi, 2018)
Candida albicans is a normal flora in several areas of the human body and has opportunistic properties, so that if conditions support, it will be able to transform into pathogens (Ramali and Werdani, 2001). Candida can become pathogenic if there are predisposing factors, one of which is diabetes mellitus (DM), the frequency of underwear replacement (Anindita, 2006) and the use of contraceptives that affect the balance of estrogen hormones (Amelia, 2009). Researchers are interested in discussing the relationship of vaginal hygiene, blood sugar levels and estrogen hormone levels with vaginalis candidiasis.The purpose of this research was to determine the relationship of vaginal hygiene, blood sugar levels and estrogen hormone levels with vaginalis candidiasis.This research is a quantitative research with a type of analytical research studies. The research design used was a cross sectional comparative study. It was carried out at the Bhayangkara Hospital Polyclinic and Padang Pasir Health Center as well as Nanggalo. The population in this research were all women of fertile age who came to the obstetric polyclinic who conducted Visual Acetate Acid (IVA) Inspection. The sample in this research is the population that meets the inclusion and exclusion criteria. The hypothesis of this research is the relationship between vaginal hygiene, blood sugar levels and estrogen hormone with vaginalis candidiasis.There is a relationship between vaginal hygiene, blood sugar levels and estrogen hormone with vaginalis candidiasis.The conclusion of this research is that the dominant factor with vaginalis candidiasis is vaginal hygiene with an OR value of 11.37.